Understanding the impact of local movies on children's behaviour: a study of violence in Polis Evo / Ezal Abdul Qaiyum Zamri ... [et al.] - Zamri, Ezal Abdul Qaiyum; Rozani, Ahmad Hanif; Roslan, Muhammad Nur Iman; Ahmad Normizan, Ahmad Fikhri; Mohammad Noor, Nurul Aliya Aisya (2018)
Purpose: This research seeks to discover how violence in local movie can affects children behaviour. The learning environments which a child is exposed are also assumed to contribute to the increase of aggressive behaviour and attitudes. Movie is one of specific learning condition is believed to be a potential contributor to the growth of antisocial behaviour in children and youth. Many studies have been conducted in the area of media violence and its effects on the young viewers. Design/methodology/approach: The Polis Evo movie storyline had been analysed based on thematic elements which include physically demonstrated violence and violent behaviour. In addition, analysis of Malaysians individuals' perspectives, definitions and usages of the term, 'violence' is done by conducting a short survey after showing the trailer for Polis Evo. An in-depth, open-ended interview with a representative of the production team of Polis Evo and a psychologist will be conducted. Findings: This research's findings helps to understand the link between watching Polis Eva's violent scenes and aggression in children as well as how violence in movies impacts children's behaviour.